Komposisi Ikan Hasil Tangkapan Bubu yang Dioperasikan di Kawasan Apartemen Ikan Perairan Desa Teluk Rhu Village Kecamatan Rupat Utara, Kabupaten Bengkalis - Brown, Arthur; Yani, Alit Hindri; Hernando, Wemphy (Jurnal Perikanan dan Kelautan, 2016)
The research was conducted on January 25th to February 3 th 2016 in Teluk Rhu Village waters of Bengkalis Regency Of Riau Provinces. This research aims to analyze the composition of traps catches and determine the type and amount of catches in the morning and afternoon at the fish aggregating device. The method used in this research is a survey and research conducted for 10 consecutive days.The catches during of research were 1,495 kg (65 ekor). The results of research on the composition of traps catches in the morning is 0,485 kg (25 fishes), while during the afternoon 1,01 kg (40 fishes). The catches is consists of four species, namely: Pseudocienna amovensis, Stromateus cinereus, Equulites leuciscus, and Chorine mustala. Afternoon catches is bigger than morning catches.